2015
DOI: 10.1016/j.juro.2014.09.107
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Dysregulation Independently Predicts Disease Specific Survival in Bladder Urothelial Carcinoma

Abstract: These results reveal that galectin-1 over expression is a possible independent factor for bladder cancer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 27 publications
2
40
0
1
Order By: Relevance
“…Based on the present data and previous studies, we propose that LGALS1 gene expression ramped up in UBUC specimens might provoke the Rac1−MEKK4−JNK signaling pathway to augment the JNK−c‐Jun−AP1−MMP9 pathway, which in turn stimulates tumor cell invasion. Our observations provide unprecedented insight into the molecular mechanism of UBUC invasiveness and metastasis.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Based on the present data and previous studies, we propose that LGALS1 gene expression ramped up in UBUC specimens might provoke the Rac1−MEKK4−JNK signaling pathway to augment the JNK−c‐Jun−AP1−MMP9 pathway, which in turn stimulates tumor cell invasion. Our observations provide unprecedented insight into the molecular mechanism of UBUC invasiveness and metastasis.…”
Section: Discussionsupporting
confidence: 74%
“…Our previous cohort study reported that Gal‐1 overexpression is significantly linked to UBUC invasion . In addition, Gal‐1 silencing inhibited the invasive ability of T24 cells and MMP9 is closely associated with tumor metastasis .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Wu et al (page 1002) from Taiwan explored the clinical significance of abnormal GAL-1 gene expression in UBUC development. 2 They selected primary localized UBUCs for which transurethral resection of bladder tumor had been done, followed by radical cystectomy for T2 to T4 tumors. Pathological slides were examined for cytoplasmic GAL-1 immunoexpression and the correlation of GAL-1 dysregulation with clinicopathological factors and disease specific survival.…”
Section: Galectin-1 Dysregulation Predicts Bladder Cancer Survivalmentioning
confidence: 99%